Z prawnej problematyki ochrony lasów we Włoszech - Flick, Giovanni Maria (Wydawnictwo Naukowe UAM, 2014)
Legal issues of forest protection in Italy S u m m a r y There is a tendency in Italy to increase forest areas, but the actual making use of forests and the quality of products obtained from them continues to be negligent. Italy is reach in poor forests and suffers all the consequences (also economic) arising from it. The author postulates making available to all operators in the forest sector, as well as to all those to whom the fate of forests is important, the necessary tools which will highlight the role of a forest as a factor of development and emphasise its importance as an element of territorial protection. These tools should be so developed as to promote an active and sustainable management of the forestry heritage being the main measure of the valuation of the forest potential as an economic as well as social, cultural and environmental instrument serving protection of the territory and local development. State functions and competences should be harmonised with those of regional and local self-governments and authorities, excessive legal regulations and bureaucracy should be eliminated, while broad synergic activity undertaken by business and environmental entities should be valued and assessed. once the legislation on forests is improved, forests will have a chance to develop and per form multiple functions, which will ultimately enable entering into the fourth phase of sustained development.

Sulla problematica giuridica della tutela dei boschi in Italia R i a s s u n t o In Italia è riscontrabile un aumento delle superfici forestali, ma al contempo si osserva una scarsa utilizzazione e una bassa qualità del prodotto da essa ritraibile. L’Italia è un paese ricco di boschi poveri con tutte le implicazioni, anche economiche che ne derivano. per questo motivo l’autore scrive tra l’altro della necessità di mettere a disposizione di tutti gli operatori del settore boschivo, nonché di tutti coloro che hanno a cuore il bosco come entità, degli strumenti che sottolineino e agevolino lo svolgimento del ruolo dei boschi, quale fattore di sviluppo ed elemento di tutela del territorio; strumenti che riconoscono nella gestione attiva e sostenibile del patrimonio forestale il mezzo principale per valorizzare le potenzialità del bosco come risorsa economica, socio-culturale e ambientale di tutela del territorio e di sviluppo locale. Occorre armonizzare fra di loro le competenze e le funzioni dello Stato e quelle delle regioni e degli enti locali; eliminare l’eccesso di produzione normativa e di burocratizzazione; valorizzare la sinergia tra la dimensione economica e quella ambientale in senso ampio. Il miglioramento dello stato della legislazione potrebbe contribuire allo sviluppo del bosco, della sua multifunzionalità, per entrare finalmente nella quarta fase, cioè nella fase dello sviluppo sostenibile.